Formaldehyde analysis of seized cosmetic products by HS-GC-MS of methylal, ethoxymethoxymethane, and ethylal derivatives - Ettore Ferrari Júnior; Lívia Barros Salum; Robiedson Romeiro Damasceno; Bárbara Elisa Pereira Alves; Eloisa Dutra Caldas (Universidade de São Paulo, 2022)
Abstract Formaldehyde is a carcinogenic compound used as preservative in cosmetic products. In this study, a derivatization procedure using MeOH, EtOH and HCl (25:25:1), and incubation at 60ºC for 4 hours was optimized, and the derivatized products - methylal, ethoxymethoxymethane (EMM), and ethylal - were directly analyzed by headspace-gas chromatography-mass spectrometry (HS-GC-MS) to determine formaldehyde concentrations. The validated method provided good linearity of the standard curve, selectivity, recovery (89.6-106.6%), repeatability, and intermediate precision (RSD < 12%), with an LOD of 0.0015% and an LOQ of 0.005% for all derivatized analytes. The validated method showed to be fast, clean, and easy to implement in a laboratory. To the best of our knowledge, this is the first reported HS-GC-MS procedure to determine formaldehyde as methylal, ethylal, and EMM as derivatized compounds. The method was satisfactorily applied for the analysis of nine hair-straightener cream samples seized by the Civil Police of the Federal District, Brazil. Eight samples contained formaldehyde, at levels ranging from 0.33 to 4.02 %, higher than the legal levels, indicating the need to control the levels of this toxic compound in cosmetic products.